Indogenous knowledge of macromycetes of the genus Amanita in Burkina Faso - Dabire, Kounbo; Sanon, Elise; Bakiono, Benovana; Barbre, Blaise; Kuisiele Somda, Andjièrèyir; Guissou, Kuilpoko Marie Laure (Ethnobotany Research and Applications, 2024)
Background: In Burkina Faso, mushrooms are used by the population for food and/or medicine. Due to accelerated population growth and anthropogenic and environmental factors, mushrooms are disappearing alarmingly. Knowledge about fungi is disappearing over time. The aim of this study is to document the state of knowledge and use of amanites by the various ethnic groups in the villages bordering the forest formations. Methods: The study was conducted in the classified forests of Niangoloko, Kou and in the gallery forest of Dan, respectively located in the provinces of Comoé, Houet and Kénédougou between 2017 and 2019. Sampling was carried out using the opportunistic or random method, and surveys were carried out using a survey form administered to interviewees individually or in groups. Ethnomycological excavations were carried out in six villages (Orodara, Tin, Dan, Yendéré, Timperba and Nasso) and involved ten ethnic groups (Gouin, Senoufo, Karaboro, Samogo, Turka, Mossi, Bobo, Dagara, Toussian and Siamou) living around the different forests. Results: The mycological digs resulted in the collection of 133 amanite carpophores, including 7 carpophores in Kou, 51 in Niangoloko and 75 in Dan. The survey was carried out among 133 people, 99 men and 34 women aged between 10 and 70. Conclusion: In general, all the ethnic groups interviewed were familiar with mushrooms, although knowledge of amanites was low. Five species of amanita (A. subviscosa, A. masasiensis, A. congolensis, A. strobiliformis, A. crassiconus) are edible and are already consumed by the local people. However, no species of amanita has been reported in the traditional medicine. Keywords: Surveys, Mycology, Traditions, socio-anthropology, Burkina Faso